Prestigious language, pigeonholed speakers: Stances towards the 'native English speaker' in a multilingual European institution. (19th August 2020) - Lovrits, Veronika; de Bres, Julia
Abstract: Critical sociolinguistics has demonstrated that the social construct of the 'native speaker' has a strong impact on people's lives, but research on 'native speaker effects' in the workplace remains rare. This article examines such effects from the perspective of four 'native English speaker' trainees on temporary contracts in a multilingual European Union institution in Luxembourg. Applying the framework of sociolinguistic stance to interview data and drawings, we examine how the participants position themselves towards the 'native English speaker' construct at work, and how they think others position them. According to our participants, 'native English speaker' positioning confers privilege but restricts opportunities, demonstrating that the interest of a multilingual organisation in using the 'native English speaker' as a resource does not automatically provide a powerful position to 'native English speaking' workers. Our results featuring trainees in precarious labour conditions raise broader issues regarding the precaritisation of language work in the EU. Résumé: Des recherches sociolinguistiques critiques ont révélé que la construction sociale de « locuteur natif» influence fortement la vie des personnes. Pourtant, les recherches concernant les « effets du locuteur natif» sur le lieu de travail sont rares. Le présent article examine ces effets depuis la perspective de quatre stagiaires « anglophones natifs» avec un contrat à durée déterminée dans une institution multilingue de l'Union européenne au Luxembourg. Appliquant le cadre de la position sociolinguistique (sociolinguistic stance) aux données des interviews et aux dessins, nous analysons comment les participants se positionnent par rapport à la construction d'« anglophone natif» au travail et comment ils se sentent positionnés par les autres. Selon nos participants, ces positionnements conféreraient des privilèges mais réduiraient également des opportunités; ainsi, l'intérêt d'une organisation multilingue à recourir à des « anglophones natifs» en tant que ressource ne place pas automatiquement ces travailleurs dans une position de pouvoir. Nos résultats – qui présentent des stagiaires en conditions de travail précaires – soulèvent des questions plus larges de précarisation du travail linguistique dans l'Union européenne.